Polymorphism Detection of GDF9 Gene and Its Association with Litter Size in Luzhong Mutton Sheep (Ovis aries) - Fengyan Wang; Mingxing Chu; Linxiang Pan; Xiangyu Wang; Xiaoyun He; Rensen Zhang; Lin Tao; Yongfu La; Lin Ma; Ran Di (Animals, 2021)
Litter size is one of the most important economic traits in sheep. GDF9 and BMPR1B are major genes affecting the litter size of sheep. In this study, the whole coding region of GDF9 was sequenced and all the SNPs (single nucleotide polymorphisms) were determined in Luzhong mutton ewes. The FecB mutation was genotyped using the Sequenom MassARRAY®SNP assay technology. Then, the association analyses between polymorphic loci of GDF9 gene, FecB, and litter size were performed using a general linear model procedure. The results showed that eight SNPs were detected in GDF9 of Luzhong mutton sheep, including one novel mutation (g.41769606 T > G). The g.41768501A > G, g.41768485 G > A in GDF9 and FecB were significantly associated with litter size in Luzhong mutton ewes. The g.41768485 G > A is a missense mutation in the mature GDF9 protein region and is predicted to affect the tertiary structure of the protein. The results preliminarily demonstrated that GDF9 was a major gene affecting the fecundity of Luzhong mutton sheep and the two loci g.41768501A > G and g.41768485 G > A may be potential genetic markers for improving litter size.